Comparison of Service Technique Effectiveness (Volley Serve vs. Drop Serve) and Its Contribution to First Point Win Percentage in Amateur Pickleball - Himawan, Ahmad; Schwemer, Leon; Damayanti, Enarnimas; Wahyu, Hardyan; Fadhillah, Rifqy; Muhammad, Farras (Journal of Racket Sports Performance & Science (JRSPS), 2025)
Background: The evolution of pickleball rules has introduced the “Drop Serve” as a legal alternative to the traditional “Volley Serve” (underhand serve). Research Objectives: This study aims to (1) Identify the frequency of use of the Volley Serve vs. the Drop Serve at the amateur level. (2) Analyze the contribution of each technique to the success of the “first point” (defined as a Service Ace or forcing a Return Error). (3) Determine whether there is a significant difference in the percentage of total rally wins based on the service technique used. Methods: This quantitative observational study analyzed 17 amateur doubles match videos (estimated level 3.0-4.0) obtained from a public video platform (YouTube), with a total of 510 serves coded. A tally sheet was used to record each serve, with the following variables: (1) Type of Serve (Volley/Drop), (2) Serve Execution (Good/Error), (3) First Point Result (Ace/Return Error/Good Return), and (4) Winner of the Rally. Results: Overhead serves are used more often (68% of 510 serves) than drop serves (32%). Drop serves show a much lower error rate (6.1%) than overhead serves (15.0%). Volley serves contributed to a slightly higher percentage of “first point” wins (14.2% of serves in) compared to drop serves (11.1%). Conclusion: There is a strategic trade-off between the aggressiveness of the Volley Serve and the consistency of the Drop Serve. For amateur players, the aggressiveness advantage of the Volley Serve appears to be negated by the high error rate, making the consistent Drop Serve an equally effective strategy.